Women explorers in polar regions : Louise Arner Boyd, Agnes Deans Cameron, Kate Marsden, Ida Pfeiffer, Helen Thayer - McLoone, Margo (Mankato, Minn. : Capstone Press, 1997)
Briefly describes the lives and travels of five women who explored the polar regions.
Includes bibliographical references (p. 45) and index.
Keywords: Women explorers -- Biography -- Juvenile literature; Explorers; Women -- Biography; Arctic Regions -- Discovery and exploration -- Juvenile literature; Arctic regions -- Discovery and exploration